2000
DOI: 10.1017/s0007114500002269
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosides and nucleotides: natural bioactive substances in milk and colostrum

Abstract: Nucleotides, nucleosides and nucleobases belong to the non-protein-nitrogen (NPN) fraction of milk. The largest amounts of ribonucleosides and ribonucleotides ± ribose forms only were considered in this review ± were measured directly after parturition in bovine milk and other ruminants as well as in the milk of humans. Generally, concentrations of most of the nucleos(t)ides tend to decrease gradually with advancing lactation period or nursing time. The species-specific pattern of these minor constituents in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(116 citation statements)
references
References 63 publications
6
107
0
3
Order By: Relevance
“…Whereas, nucleotides administration influenced significantly (P < 0.001) the ether extract content, showing higher values in the N group than in the C group; this could be related to the physiologic effect of nucleotides to stimulate the plasmatic α-lipoprotein synthesis (Schlimme et al 2000;Mateo & Stein 2007) and to increase the haematic levels of high density lipoprotein during the neonatal period (Sanchez-Pozo et al 1996).…”
Section: Nutritional Characteristics Of the Meatmentioning
confidence: 95%
See 1 more Smart Citation
“…Whereas, nucleotides administration influenced significantly (P < 0.001) the ether extract content, showing higher values in the N group than in the C group; this could be related to the physiologic effect of nucleotides to stimulate the plasmatic α-lipoprotein synthesis (Schlimme et al 2000;Mateo & Stein 2007) and to increase the haematic levels of high density lipoprotein during the neonatal period (Sanchez-Pozo et al 1996).…”
Section: Nutritional Characteristics Of the Meatmentioning
confidence: 95%
“…A hypothesis could be considered that nucleotide supplementation stimulated the intestinal or he- patic synthesis of the elongation enzymes and all the desaturase enzymes (∆9-,∆6-, ∆5-desaturase) as a result of increased protein synthesis (Gil et al 1986;Garcia-Molina et al 1991) for the metabolic conversion of acidic products as reported by Schlimme et al (2000) but: (i) in relation to the individual fatty acid levels and (ii) in relation to the affinity of the desaturase enzymes with the fatty acid classes, the effect of stimulation was remarkable only for the ∆-9-desaturase. These findings suggest that no induction occurred of long chain polyunsaturated fatty acid accumulation in Pectoralis major muscle owing to the dietary supplementation with nucleotides in accordance to Gibson et al (2005) observations.…”
Section: Nutritional Characteristics Of the Meatmentioning
confidence: 99%
“…Nucleotides and nucleosides comprise part of the non-protein-nitrogen (NPN) fraction of milk and are present in the sub-milligram range per litre (Schlimme et al 2000); they have important roles in biochemical synthesis, i.e. nucleic acid synthesis, enhancement of immune response (Schaller et al 2004), influence the metabolism of fatty acids, contribute to iron absorption in the gut and improve gastrointestinal tract repair after damage (Sanchez-Pozo and Gill 2002).…”
Section: Nucleotides and Nucleosidesmentioning
confidence: 99%
“…Human milk contains at least 13 acid-soluble nucleotides, cytidine and uridine derivatives being quantitatively the most important. It also contains minor amounts of free nucleosides (15). In contrast, bovine milk has a low content of nucleotides (13).…”
mentioning
confidence: 99%